Marketing Communication: Pengalaman Pebisnis Pemula Dalam Melakukan Branding - Fatmawati Moekahar; Benni Handayani; Yudi Daherman; Mufti Hasan Alfani (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2020)
Branding is an important factor for every businessman in the sustainability of his business. The Big brands become alternative choices for consumers in determining the products they want to buy. Therefore a brand is built with a relatively long period of time for businessman. However, for the Beginner businessman, often the brand is not a priority. They only care about how much the products they sell are in demand and are bought by consumers regardless of the brand name of the product itself. This study aims to determine the branding process carried out by the beginner businessman. Researchers look at this problem from the perspective of marketing communication. The research method used is qualitative with a phenomenological approach. Informants consisted of 20 students/graduated who are beginner businessman. The characteristics of a beginner businessman are determined at least one year of the business being run, and are the first-time businessman to have a business. The results of this study found that the branding experience of beginner businessman is done in two ways namely the name and the sign that is used as the closest identity to the product. Whereas marketing communication carried out by beginner businessmen in branding includes communication through social media, word of mouth communication, network communication, which aims to persuade consumers, build impressions and maintain customer loyalty with a simple and limited approach.